Las oportunidades de estudio como incentivo: Los jóvenes de Solidaridad Nacional y la militancia partidaria en el Perú contemporáneo - Ayala Abril, Henry (2016)
Participation through a political party is declining globally (Dalton & Wattenberg 2000). Instead, new, more horizontal forms of politics have emerged which undermine the mobilization capacity of parties (Cross & Young 2008). In Latin America, along with it, informality and the establishment of direct links between the leader and his followers are elements that further weaken the identification with a party organization. Nevertheless, parties persist, surviving from their precarious institutionality and adapting their strategies to obtain a base of militants that support the organization. How to understand this decision of participating in a political party in a context that discourages it?This article discusses the incentives for young people to choose to be militants in a Peruvian personalist party. For this, it studies the case of young people on Solidaridad Nacional party in Lima; an organization that, under the leadership of José Luna Gálvez in 2014, implemented a youth recruitment strategy that adapted the militant supply to the various motivations they had as altruist goals, a political career or opportunities for study or work. Thus, the study highlights the use of Diplomados Solidarios in charge of Telesup University for the recruitment and identification of militants, as well as the importance of altruistic motivations and social norms that attracts young people during the process of political socialization.